Aspirations in a warming world: Modeling migration and education decisions under climate risk in Senegal - Nicolas Choquette-Levy; Fabien Cottier; Ndèye Coumba Diouf; Aboubakr Gambo Boukary; Véronique Petit; Etienne Piguet; Seynabou Sall; Corentin Visée; Alex de Sherbinin; Andrew Reid Bell (Global Environmental Change, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Ascorbic acid mediated hydrolysis of galactomannans - Michael-Alex Kamlow; Julian Marks; Joshua E.S.J. Reid; Vlad Dinu; Ian D. Fisk; Gleb E. Yakubov (Food Hydrocolloids, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Greenhouse Gas Emission Menu Icons Decrease Service of All Menu Items in Residential Dining Halls at a Large, Midwestern Public US University - Andrew D. Jones; Lesli Hoey; Cindy W. Leung; Melissa J. Slotnick; Wei Hao; Kitty Oppliger; Alex Bryan; Steve Giardini; Ha Young Kim; Steve Mangan; Hailey McQuaid; Melanie Reid; et al. (Journal of the Academy of Nutrition and Dietetics, 2026)

Tail-less precursors in synthetic cannabinoid production: investigating a clandestine laboratory, seized samples, and CB1 activity - Manuela Carla Monti; Tobias Rautio; Marie H. Deventer; Markus Schläpfer; Johannes Tveit; Alex J. Krotulski; Victoria Marland; Robert Reid; Niamh Nic Daeid; Craig McKenzie; Christophe P. Stove; Henrik Green; et al. (Archives of Toxicology, 2025)
An emerging new trend reveals that potent synthetic cannabinoid receptor agonists (SCRAs) that were prevalent prior to the Chinese class-wide ban in July 2021 have remained on the market or re-emerged. This is likely because of a new production route where unscheduled tail-less precursors are converted into the desired controlled SCRA via a one-step synthesis. This study reports the discovery of a clandestine production site in Switzerland for this synthesis. Controlled recreations of the synthesis of ADB-BUTINACA (also known as ADB-BINACA or ADMB-BUTINACA) and MDMB-4en-PINACA based on a recipe recovered from the Swiss production site were undertaken. The recreations yielded oils or waxy products with chromatographic purities ranging from 39.3 to 93.4% with the precursors (ADB-INACA or MDMB-INACA) remaining in all products. Mixtures of a precursor (e.g., MDMB-INACA, ADB-INACA, AB-INACA, MDMB-ICA, ADB-IATA, MDMB-5’Me-INACA) with corresponding final SCRA(s) (e.g., MDMB-4en-PINACA, 4F-MDMB-BUTINACA, MDMB-BUTINACA, MDMB-FUBINACA, ADB-BUTINACA, ADB-4en-PINACA, AB-CHMINACA, 4F-MDMB-BUTICA, ADB-FUBIATA) were found in 28 forensic casework samples in the US received between February 2023 and February 2024 and 87 samples seized from the Scottish prisons between February 2023 and July 2024. In vitro CB 1 receptor activity of the precursors, synthesized products, and mixtures of precursors and final SCRAs were examined using β-arrestin 2 recruitment and intracellular calcium release assays. The precursors were much less potent than the final SCRAs and the concentration of the final SCRA dictated the activity of mixtures. This study raises awareness of the emergence of a new production method for SCRAs as observed in multiple countries.

Community Structure, Health Status and Environmental Drivers of Coral Reefs in Koh Seh Island of the Kep Archipelago, Cambodia - Srey Oun Ith; Amick Haissoune; Alex Reid; Ratha Sor (Journal of Marine Science and Engineering, 2025)
Coral reef ecosystems are home to diverse marine flora and fauna. However, these ecosystems are threatened by an array of environmental and anthropogenic factors. Here, we investigated coral reef diversity, structure, and health status, and identified their key environmental drivers. Coral reef data were collected from Koh Seh Island, located inside the Marine Fisheries Management Area in the Kep archipelago. We found that the reef cover largely comprised live corals (64%, mainly Porites and Tubinaria species), followed by Zoanthids (15%) and sand/rubble (15%). Based on Ward’s hierarchical cluster analysis, coral communities were grouped into three zones: East, South, and West zones. Coral diversity was slightly higher in the East zone, though not statistically significant. Zone East showed a positive association with sediment loads and water temperature. Elevated levels of salinity, dissolved oxygen, and pH were characteristic of the East and South zones, whereas the West zone was distinguished by deeper water conditions. We also found that Favites was the key indicator for coral communities in the East zone, which features shallow, high-DO, high-pH waters with more sediments, strong currents, and significant human activities like fishing and transportation. Goniastrea species were abundant in the South and East zones, making it the indicator taxon, while the West zone had no indicator, suggesting that coral species are sparse in this zone. Interestingly, only a few dead corals were found, and no signs of diseases were detected around the Koh Seh coral reefs. This may reflect the effectiveness of joint protection efforts by Marine Conservation Cambodia and the Marine Fisheries Department in Kep province. Overall, our study provides a valuable baseline for assessing future changes in benthic reefs and coral communities on Koh Seh island, throughout the Kep Archipelago and its surrounding areas.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Testing in-situ apatite Lu–Hf dating in polymetamorphic mafic rocks: a case study from Palaeoproterozoic southern Australia - Dillon A. Brown; Anthony Reid; Elizabeth A. Jagodzinski; Megan Williams; Alex Simpson; Mark Pawley; Christopher L. Kirkland; Claire Wade; Alexander T. De Vries Van Leeuwen; Stijn Glorie (Contributions to Mineralogy and Petrology, 2024)
In mafic systems where primary mineral assemblages have witnessed moderate- to high-temperature hydrous overprinting and deformation, little is known about the retentivity of the Lu–Hf isotopic system in apatite. This study presents apatite laser-ablation Lu–Hf and U–Pb geochronology, zircon geochronology, and detailed petrological information from polymetamorphic mafic intrusions located in the central-western Gawler Craton in southern Australia, which records an extensive tectonometamorphic history spanning the Neoarchaean to the Mesoproterozoic. Zircon records magmatic crystallisation ages of c. 2479–2467 Ma, coinciding with the onset of the c. 2475–2410 Ma granulite-facies Sleafordian Orogeny. The amphibole-dominant hydrous assemblages which extensively overprint the primary magmatic assemblages are hypothesised to post-date the Sleafordian Orogeny. The Lu–Hf and U–Pb isotopic systems in apatite are used to test this hypothesis, with both isotopic systems recording significantly younger ages correlating with the c. 1730–1690 Ma Kimban Orogeny and the c. 1590–1575 Ma Hiltaba magmatic event, respectively. While the early Mesoproterozoic apatite U–Pb ages are attributed to thermal re-equilibration, the older Lu–Hf ages are interpreted to reflect re-equilibration facilitated primarily by dissolution-reprecipitation, but also thermally activated volume diffusion. The mechanisms of Lu–Hf isotopic resetting are distinguished based on microscale textures and trace element abundances in apatite and the integration of apatite-amphibole textural relationships and temperatures determined from the Ti content in amphibole. More broadly, the results indicate that at low to moderate temperatures, apatite hosted in mafic rocks is susceptible to complete recrystallisation in rocks that have weak to moderate foliations. In contrast, at higher temperatures in the absence of strain, the Lu–Hf system in apatite is comparatively robust. Ultimately, the findings from this study advance our understanding of the complex role that both metamorphism and deformation play on the ability of mafic-hosted apatite to retain primary Lu–Hf isotopic signatures.

Establishing effective conservation management strategies for a poorly known endangered species: a case study using Australia’s Night Parrot (Pezoporus occidentalis) - Nicholas P. Leseberg; Alex Kutt; Megan C. Evans; Tida Nou; Scott Spillias; Zoe Stone; Jessica C. Walsh; Stephen A. Murphy; Mike Bamford; Allan H. Burbidge; Kate Crossing; Robert A. Davis; et al. (Biodiversity and Conservation, 2023)
An evidence-based approach to the conservation management of a species requires knowledge of that species’ status, distribution, ecology, and threats. Coupled with budgets for specific conservation strategies, this knowledge allows prioritisation of funding toward activities that maximise benefit for the species. However, many threatened species are poorly known, and determining which conservation strategies will achieve this is difficult. Such cases require approaches that allow decision-making under uncertainty. Here we used structured expert elicitation to estimate the likely benefit of potential management strategies for the Critically Endangered and, until recently, poorly known Night Parrot ( Pezoporus occidentalis ). Experts considered cat management the single most effective management strategy for the Night Parrot. However, a combination of protecting and actively managing existing intact Night Parrot habitat through management of grazing, controlling feral cats, and managing fire specifically to maintain Night Parrot habitat was thought to result in the greatest conservation gains. The most cost-effective strategies were thought to be fire management to maintain Night Parrot habitat, and intensive cat management using control methods that exploit local knowledge of cat movements and ecology. Protecting and restoring potentially suitable, but degraded, Night Parrot habitat was considered the least effective and least cost-effective strategy. These expert judgements provide an informed starting point for land managers implementing on-ground programs targeting the Night Parrot, and those developing policy aimed at the species’ longer-term conservation. As a set of hypotheses, they should be implemented, assessed, and improved within an adaptive management framework that also considers the likely co-benefits of these strategies for other species and ecosystems. The broader methodology is applicable to conservation planning for the management and conservation of other poorly known threatened species.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Single nucleotide polymorphism assay to distinguish barley (Hordeum vulgare L.) varieties in support of seed certification - Heather Owen; Karen Pearson; Adrian M. I. Roberts; Alex Reid; Joanne Russell (Genetic Resources and Crop Evolution, 2019)

Does Regional Development Influence Sedimentary Blue Carbon Stocks? A Case Study From Three Australian Estuaries - Stephen Conrad; Dylan R. Brown; Paula Gomez Alvarez; Bronte Bates; Nizam Ibrahim; Alex Reid; Luciana Silva Monteiro; Daniela A. Silva; Lea T. Mamo; Jacob R. Bowtell; Huang An Lin; Nathaniel L. Tolentino; et al. (Frontiers in Marine Science, 2019)

Genetic Diversity and Redundancy Among Potato Accessions in the Montenegrin Collection as Revealed by Microsatellite Markers - Marko Maras; Aleš Sedlar; Alex Reid; Vladan Božović; Zoran Jovović; Vladimir Meglič; Peter Dolničar (American Journal of Potato Research, 2017)

A metagenetic approach to determine the diversity and distribution of cyst nematodes at the level of the country, the field and the individual - Sebastian Eves‐van den Akker; Catherine J. Lilley; Alex Reid; Jon Pickup; Eric Anderson; Peter J.A. Cock; Mark Blaxter; Peter E. Urwin; John T. Jones; Vivian C. Blok (Molecular Ecology, 2015)
Distinct populations of the potato cyst nematode ( PCN ) Globodera pallida exist in the UK that differ in their ability to overcome various sources of resistance. An efficient method for distinguishing between populations would enable pathogen‐informed cultivar choice in the field. Science and Advice for Scottish Agriculture ( SASA ) annually undertake national DNA diagnostic tests to determine the presence of PCN in potato seed and ware land by extracting DNA from soil floats. These DNA samples provide a unique resource for monitoring the distribution of PCN and further interrogation of the diversity within species. We identify a region of mitochondrial DNA descriptive of three main groups of G. pallida present in the UK and adopt a metagenetic approach to the sequencing and analysis of all SASA samples simultaneously. Using this approach, we describe the distribution of G. pallida mitotypes across Scotland with field‐scale resolution. Most fields contain a single mitotype, one‐fifth contain a mix of mitotypes, and less than 3% contain all three mitotypes. Within mixed fields, we were able to quantify the relative abundance of each mitotype across an order of magnitude. Local areas within mixed fields are dominated by certain mitotypes and indicate towards a complex underlying ‘pathoscape’. Finally, we assess mitotype distribution at the level of the individual cyst and provide evidence of ‘hybrids’. This study provides a method for accurate, quantitative and high‐throughput typing of up to one thousand fields simultaneously, while revealing novel insights into the national genetic variability of an economically important plant parasite.

Evaluation of Simple Sequence Repeat (SSR) Markers Established in Europe as a Method for the Identification of Potato Varieties Grown in Canada - Marie-José Côté; Lisa Leduc; Alex Reid (American Journal of Potato Research, 2013)